Psychopathologie et sport de haut niveau - Salmi, M.; Pichard, C.; Jousselin, E. (Science & Sports, 2010)
Context Practicing sport regularly provides obvious benefits in health in the broad sense of the term. However, intensive sport activity in particular for high level athletes require vigilance as well as a specific somatic and psychological follow-up.